2016
DOI: 10.1007/s00345-016-1879-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nocturnal enuresis and related risk factors in school-age children in Egypt: an epidemiological study

Abstract: In the Egyptian community, pinworm infestation, UTI, constipation, and overconsumption of caffeine-containing beverages are potential reversible risk factors for MNE in school-age children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
72
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 26 publications
14
72
3
1
Order By: Relevance
“…The global incidence of enuresis in children 6-12 years of age was shown to be 15%-25% in one study [3]. While a study in Egypt showed an incidence of 18% among children 9 ± 2 years old [4].…”
Section: Introductionmentioning
confidence: 94%
“…The global incidence of enuresis in children 6-12 years of age was shown to be 15%-25% in one study [3]. While a study in Egypt showed an incidence of 18% among children 9 ± 2 years old [4].…”
Section: Introductionmentioning
confidence: 94%
“…The risk factors related to NE reported in different studies include constipation, positive family history, obstructive respiratory disorder, deep sleep, corporal punishment at school, urinary tract infection, etc. [3][4][5][6]. However, the effect of each factor on NE varies from study to study, and no universal conclusion is drawn.…”
Section: Epidemiologymentioning
confidence: 99%
“…Так, у заражених гельмінтами S. obvelata мишей спостерігалося зменшення дослідницької поведінки [5]. Таким чином, клінічні та експериментальні дані вказують на те, що гострикова інвазія може негативно впливати на центральну нервову систему, що може призводити до неврологічних порушень [6,7]. На жаль дослідження впливу ентеробіозу на поведінкові реакції господаря є поодинокими і найчастіше мають ретроспективний, описовий характер.…”
Section: вступunclassified